2022
DOI: 10.3168/jds.2022-22135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wildfire smoke exposure on innate immunity, metabolism, and milk production in lactating dairy cows

Abstract: Wildfires are particularly prevalent in the Western United States, home to more than 2 million dairy cows that produce more than 25% of the nation's milk. Wildfires emit fine particulate matter (PM 2.5 ) in smoke, which is a known air toxin and is thought to contribute to morbidity in humans by inducing inflammation. The physiological responses of dairy cows to wildfire PM 2.5 are unknown. Herein we assessed the immune, metabolic, and production responses of lactating Holstein cows to wildfire PM 2.5 inhalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 66 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…15 There is also increasing evidence that heat stress and other climatic changes have clinically relevant impacts on dairy cows and are likely to become greater issues in much of the US in the coming years. 16,17 Clearly, there are many questions about the impacts of animal health on environmental sustainability and there remains a sizable need for research to address these questions.…”
Section: Introductionmentioning
confidence: 99%
“…15 There is also increasing evidence that heat stress and other climatic changes have clinically relevant impacts on dairy cows and are likely to become greater issues in much of the US in the coming years. 16,17 Clearly, there are many questions about the impacts of animal health on environmental sustainability and there remains a sizable need for research to address these questions.…”
Section: Introductionmentioning
confidence: 99%
“…Other health metrics provide a more nuanced picture of the effects of smoke in particular on large animal health. For example, a recent study directly linked exposure to PM 2.5 from wildfire smoke to negative health effects in dairy cows, including reduced milk production, altered metabolism, and changes in blood immune cell composition (Anderson et al 2022), and a study of captive rhesus macaque monkeys (Macaca mulatta) found that exposure to smoke as infants led to reduced lung volume as adolescents (Black et al 2017). Case studies from veterinary medicine indicate respiratory and neurological effects of smoke exposure for cats (Felis catus) and dogs (Canis familiaris) (Drobatz et al 1999a, b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, farm animals exposed to smoke show low conception rates, poor weight gain, and decreased milk production. 15 Likewise, 2-to-3-month-old captive infant rhesus macaques ( Macaca mulatta ) exposed to 10 days of high particulate matter (PM 2.5 = particles measuring < 2.5 μm in diameter) concentrations from wildfire smoke showed reduced lung capacity and weakened immune responses at age three. 16 In that same colony of macaques, pregnant females who were exposed to 12 consecutive days of elevated PM 2.5 concentrations (i.e., exceeding 35 μg/m 3 ) experienced greater pregnancy loss compared to females who were pregnant during periods of healthy air.…”
Section: Introductionmentioning
confidence: 99%